Human-elephant conflict in communities bordering Kruger National Park: Revealing causes and unpicking social media narratives - Tom P. Moorhouse; Herbert Ntuli; Prince Nketiah; Angie Elwin; Suzi Paterson; Neil C. D’Cruze (PLoS ONE, 2026)
Conflict between humans and wildlife in communities living adjacent to protected areas is one of the most intractable issues facing policymakers and conservation practitioners. The presence of wildlife can negatively impact on humans in a number of different ways, from fatalities to loss of livelihoods. Proximity to human communities can also negatively impact wildlife, for example through retaliatory killings and illegal harvesting. Meeting conservation objectives therefore often requires measures to reduce human-wildlife conflict, especially at the borders of national parks. We examine the drivers of human-elephant conflict occurring in villages bordering Kruger National Park (KNP), South Africa – which can result in the killing of elephants that enter these communities. We use data from surveys in these communities, as well as online descriptions of an incident in the village of Matsulu which resulted in the death of an elephant and which was filmed by several community members, generating a large number of social media stories. Social media stories and survey responses both highlighted the same underlying drivers of elephant killings: that members of the community appear to have tampered with the KNP fence and encouraged elephants to exit the park. Community members benefited through obtaining elephant meat. Data from the survey additionally indicated that a small number of community members profit financially from elephant escapes, but that the wider community experiences a range of negative impacts, which may be partially defrayed by benefits in the form of meat. The majority (71.2%) of survey respondents stated they would support non-lethal elephant management approaches. The current policy regarding elephant management in KNP is that elephants are protected within the park but if outside and considered a danger to humans are permitted to be killed. This policy has implications for elephant conservation in a context where members of local communities may feel incentivised to facilitate the escape of elephants, in order to benefit from legitimately killing them. We recommend an evaluation of this policy in the light of community attitudes towards elephants and their management.